2013
DOI: 10.1371/journal.pone.0082379
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Mediates Ox-LDL-Induced Human Vascular Smooth Muscle Cell Calcification via p38 Mitogen-Activated Protein Kinase Signaling

Abstract: Vascular calcification is associated with significant cardiovascular morbidity and mortality, and has been demonstrated as an actively regulated process resembling bone formation. Oxidized low density lipoprotein (Ox-LDL) has been identified as a regulatory factor involved in calcification of vascular smooth muscle cells (VSMCs). Additionally, over-expression of recombinant human neutral sphingomyelinase (N-SMase) has been shown to stimulate VSMC apoptosis, which plays an important role in the progression of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 47 publications
4
74
2
Order By: Relevance
“…C). Previous studies reported that a treatment with 100 μg/mL oxLDL induced cell apoptosis and calcification, while that with 50 μg/mL oxLDL induced cell migration and proliferation in VSMCs [Zhao et al, ; Ding et al, ; Liao et al, ]. In the present study, 100 μg/mL oxLDL, but not 50 μg/mL significantly induced cell damage from the results of MTT assay, LDH release and trypan blue staining (Fig.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…C). Previous studies reported that a treatment with 100 μg/mL oxLDL induced cell apoptosis and calcification, while that with 50 μg/mL oxLDL induced cell migration and proliferation in VSMCs [Zhao et al, ; Ding et al, ; Liao et al, ]. In the present study, 100 μg/mL oxLDL, but not 50 μg/mL significantly induced cell damage from the results of MTT assay, LDH release and trypan blue staining (Fig.…”
Section: Resultssupporting
confidence: 57%
“…and ). A treatment with 100 μg/mL oxLDL has been reported to induce apoptosis in and the calcification of VSMCs, whereas that with 50 μg/mL oxLDL induced cell proliferation in human VSMCs [Zhao et al, ; Ding et al, ; Liao et al, ]. In the present study, 100 μg/mL, but not 50 μg/mL oxLDL significantly induced cell damage (Fig.…”
Section: Discussionsupporting
confidence: 44%
“…In another study, oxidized low density lipoprotein (Ox‐LDL) stimulated phosphorylation of p38 in cultured human VSMCs, resulting in apoptosis and VC. By contrast, inhibitor for p38 significantly attenuated these effects (Liao et al, ). Speer et al () found that VSMCs incubated with indoxyl sulfate (IS) showed a significant increase of calcium deposition, BMP2, and Pit‐1 expression, paralleled by activating JNK signaling.…”
Section: Potential Signaling Pathways Affected By Pdgf To Accelerate Vcmentioning
confidence: 98%
“…BMP2 [69, 7577] as well as RUNX2 [78] and MSX2 [79] expression in vascular cells, including AV derived vascular interstitial cells (VIC), are up-regulated following exposure to OxLDL. OxLDL exposure also suppresses osteoprotegerin [80], an inhibitor of vascular calcification via the RANK-L pathway [81, 82].…”
Section: Mechanisms For Lp(a) and Oxpl Towards Av Calcification And Tmentioning
confidence: 99%
“…OxLDL exposure also suppresses osteoprotegerin [80], an inhibitor of vascular calcification via the RANK-L pathway [81, 82]. Finally, exposure to OxLDL in vitro stimulates extracellular matrix calcium deposition by vascular cells [78, 79, 83, 84] as well as up-regulation of alkaline phosphatase (ALP) [67, 79, 83, 85, 86] promoting mineralization.…”
Section: Mechanisms For Lp(a) and Oxpl Towards Av Calcification And Tmentioning
confidence: 99%